METHODOLOGY FOR ASSESSING THE GEOECOLOGICAL CONDITION OF URBANIZED AREAS (Uzbekistan Open Conference, 2025)
This article analyzes the methodology of geoecological assessment of urbanized areas through scientific-theoretical foundations and practical approaches. The study examines concepts developed by international scholars, as well as the tasks outlined in the decrees and resolutions of the President of the Republic of Uzbekistan regarding the ecological consequences of urbanization processes. Methods for calculating the anthropogenic pressure index in urban areas, improving the geoecological monitoring system, and developing sustainable development strategies are highlighted. The results of the article contribute to ensuring environmental safety in urbanized territories and implementing the “green cities” concept.